Korelasi Kuat Tekan dengan Kuat Geser pada Tanah Lempung yang Didistribusi dengan Variasi Campuran Pasir - Pratama, Albertus Willy; Iswan, Iswan; Jafri, Muhammad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
This research aims to determine the compressive strength and shear strength on clay which issubstituted with a mixture of sand variations. Soil tested in this study is derived from clay ofBelimbing Sari Village, Jabung District, East Lampung. This is done because if you set up astructure on top of the clay will cause some problems, among others, the small value ofcompressive strength and shear strength of the soil.To determine the effect of mixing clay with sand on the compressive strength and shear strength, itis done by varying the mixing of sand by 10%, 20%, 30%, 40%. From the test results it is obtainedthat the increase in shear strength to a maximum of 0.7534 kg / cm2 and a decrease in cohesionvalue of 0.10 kg / cm2 at mixing the sand as much as 40%. In the compressive strength reaches amaximum value at 30% of the mixing done 4 variation is equal to 0.4996 kg / cm3. The greater thelevel of sand were added then the lesser the value of the soil cohesion, friction angle and thecompressive strength will increase although the maximum compressive strength value in mixing30% sand.Keywords : Clay, Sand, Soil Compressive Strength, Soil Strength Press